Non-common priors, incentives, and promotions: The role of learning - Matthias Fahn; Nicolas Alexandre Klein (Johannes Kepler University of Linz, Department of Economics, 2023)
Consider a repeated principal-agent setting with verifiable effort and an extra profit that can materialize only if the agent is talented. The agent is overconfident and updates beliefs using Bayesâ exteuro™ rule. The agent's principal-expected compensation decreases over time until high talent is revealed; thus he may be employed only if beliefs are sufficiently low. We apply these results to a firm's promotion policy, which may be based on success in a previous job even if jobs are uncorrelated. This provides an explanation for the "Peter Principle" in a setting with verifiable performance and highly confident workers (Benson et al., 2019).
Keywords: 330; Personalmanagement; Erwerbsverlauf; Prinzipal-Agent-Theorie; Wiederholte Spiele; Lernprozess; Hochqualifizierte Arbeitskräfte; Theorie